Bone mineralisation in preterm infants measured by dual energy radiographic densitometry. Issue 7 (July 1989) - Lyon, A J; Hawkes, D J; Doran, M; McIntosh, N; Chan, F
Abstract : Dual energy radiographic densitometry was used to follow postnatal changes in the bone mineral content of the radii of 15 infants of less than 30 weeks' gestation. The system permitted bone mineral content to be measured with minimal disturbance to the infants in their incubators. Mean bone mineral content at birth was 2.4 mg/mm shaft length, decreasing to 1.9 mg/mm at 6 weeks of age, before starting to rise. Mineralisation was poor compared with that of a fetus at an equivalent postconceptual age. Mean intakes of calcium and phosphate were considerably less than the intrauterine accumulation of these minerals and it is postulated that this was the main cause of the poor mineralisation. Radiographic densitometry is both accurate and precise and has advantages over photon absorptiometry in that it can be used to measure bone mineral in infants who are not only preterm, but also ill enough to require intensive care.